2021
DOI: 10.1152/ajpcell.00059.2021
|View full text |Cite
|
Sign up to set email alerts
|

Diseases caused by mutations in the Na+/K+ pump α1 gene ATP1A1

Abstract: Human cell survival requires function of the Na+/K+ pump; the heteromeric protein that hydrolyzes ATP to extrude Na+ and import K+ across the plasmalemma, thereby building and maintaining their electrochemical gradients. Numerous dominant diseases caused by mutations in genes encoding for Na+/K+ pump catalytic (α) subunit isoforms highlight the importance of this protein. Here, we review literature describing disorders caused by missense mutations in ATP1A1, the gene encoding the ubiquitously expressed α1 isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 114 publications
0
15
0
Order By: Relevance
“…6 ATP1A1 protein and respective locations of the pathogenic variants reported up to date. Variants written in black represent CMT related variants identified in other studies, red represents the ATP1A1 variant identified in this study, blue represent hypomagnesaemia and intellectual disability or spastic paraplegia, green represent developmental delay, orange represent complex neurodevelopmental syndrome diseases associated with Na + /K + ATPase mutations [34]. Mitochondria are essential for buffering intracellular Ca 2+ .…”
Section: Discussionmentioning
confidence: 77%
“…6 ATP1A1 protein and respective locations of the pathogenic variants reported up to date. Variants written in black represent CMT related variants identified in other studies, red represents the ATP1A1 variant identified in this study, blue represent hypomagnesaemia and intellectual disability or spastic paraplegia, green represent developmental delay, orange represent complex neurodevelopmental syndrome diseases associated with Na + /K + ATPase mutations [34]. Mitochondria are essential for buffering intracellular Ca 2+ .…”
Section: Discussionmentioning
confidence: 77%
“…In addition, homozygous truncating variants of ATP1A2 would cause a novel lethal recognizable polymicrogyria syndrome. Polymicrogyria is responsible for a wide range of neurological symptoms, including epilepsy 36–38 . The mechanism under epileptogenicity of polymicrogyria remains unknown.…”
Section: Na+‐k+‐atpase and Seizures/epilepsy: Evidence From Bench And...mentioning
confidence: 99%
“…Polymicrogyria is responsible for a wide range of neurological symptoms, including epilepsy. 36 , 37 , 38 The mechanism under epileptogenicity of polymicrogyria remains unknown. However, unilateral multilobar polymicrogyria is often relevant to an age‐related syndrome of epilepsy.…”
Section: Na+‐k+‐ Atpase and Seizures/epilepsy: Evi...mentioning
confidence: 99%
“…Heterozygous loss-of-function, with a missense variant that partially reduces Na + /K +transport by the gene product of one allele, has been proposed to cause some ATP1A1 disease phenotypes. Electrophysiological studies in Xenopus oocytes and adrenal NCI-H295R cells expressing disease-related NKA α1 variants reported depolarizing inward currents through most (but not all) variants linked to hyperaldosteronism (2,8,10,11) or hypomagnesemia with refractory seizures (7,12), providing a plausible gain-of-function mechanism for these diseaseassociated variants. However, variants causing neuropathies seem to lack such inward "leak" currents (4)(5)(6)(7)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%